Upper Ordovician conodont biostratigraphy and revised lithostratigraphy and geological map, Akpatok Island, Ungava Bay, Nunavut - Zhang, Shunxin (NRC Research Press (a division of Canadian Science Publishing), 2017)
Stratigraphic units exposed on Akpatok Island, Ungava Bay, Nunavut, were previously recognized as Boas River and Akpatok formations; their biostratigraphic ages and correlations, in particular the stratigraphic position and age of the organic rich “Boas River” Formation, were largely based on limited data. New detailed field observations have recognized three stratigraphic units, namely the Amadjuak, Akpatok and Foster Bay formations, in which extensive microfossil sampling recovered over 22 000 conodont elements from 66 productive samples from both outcrops and rubble at over 20 localities in four areas. Four Upper Ordovician conodont zones and one unzoned interval are established for the three redefined formations: Belodina confluens and Oulodus velicuspis Interval zones are confined to the exposed Amadjuak Formation and correlated to Edenian and Maysvillian; Amorphognathus ordovicicus-Plegagnathus dartoni Concurrent-range Zone occurs with the Akpatok Formation and correlated to lower Richmondian; and Rhipidognathus symmetricus Taxon-range Zone is retained in the Foster Bay Formation and correlated to upper Richmondian; and an “Unzoned Interval” is defined between that last two zones in the lower Foster Bay Formation. The conodont Amorphognathus ordovicicus occurs in both Akpatok and lower Foster Bay formations, and it is also recovered from the bituminous, argillaceous limestone rubble, based on which the stratigraphic position of the previously named “Boas River” Formation is most likely positioned within the lower Foster Bay Formation. The biostratigraphy and lithostratigraphy are combined with geographic information systems (GIS) to establish the thicknesses of the three formations and revise the geologic map of the island. The accepted manuscript in pdf format is listed with the files at the bottom of this page. The presentation of the authors' names and (or) special characters in the title of the manuscript may differ slightly between what is listed on this page and what is listed in the pdf file of the accepted manuscript; that in the pdf file of the accepted manuscript is what was submitted by the author.